2017
DOI: 10.3892/ol.2017.5715
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the seleno-transcriptome expression between human non-cancerous mammary epithelial cells and two human breast cancer cell lines

Abstract: Abstract. Breast cancer is the second most common cause of mortality in women; therefore, the identification of novel putative markers is required to improve its diagnosis and prognosis. Selenium is known to protect mammary epithelial cells from oxidative DNA damage, and to inhibit the initiation phase of carcinogenesis by stimulating DNA repair and apoptosis regulation. Consequently, the present study has focused attention on the selenoprotein family and their involvement in breast cancer. The present study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Despite these negative findings, upregulation of DIO1, DIO2 and DIO3 mRNAs has been shown in MCF-7 cells. On the other hand, only DIO2 is upregulated in MDA-MB-231 when these cell lines were compared to non-tumoral human breast cells MCF-10A (Rusolo et al 2017). The differences between deiodinase mRNA expression and protein activity could be explained by different subtypes of breast tumor as well as posttranscriptional regulatory mechanisms.…”
Section: Breast Cancer: Deiodinases As Markers or Effectors?mentioning
confidence: 92%
“…Despite these negative findings, upregulation of DIO1, DIO2 and DIO3 mRNAs has been shown in MCF-7 cells. On the other hand, only DIO2 is upregulated in MDA-MB-231 when these cell lines were compared to non-tumoral human breast cells MCF-10A (Rusolo et al 2017). The differences between deiodinase mRNA expression and protein activity could be explained by different subtypes of breast tumor as well as posttranscriptional regulatory mechanisms.…”
Section: Breast Cancer: Deiodinases As Markers or Effectors?mentioning
confidence: 92%
“…Although the active domain of GPx5 lacks selenocysteine, it retains antioxidant properties [18]. Another non-selenium glutathione peroxidase, GPx7, which lacks GPx activity, has recently been described as a novel phospholipid hydroperoxide GPx [11,[19][20][21]; the sequence of GPx7 encodes cysteine in its conserved catalytic motifs [22]. As a non-selenocysteine, GPx8 is a membrane protein that is detected in the endoplasmic reticulum, is present abundantly expressed in the lung, and was identified as a novel member of the GPx family [23].…”
Section: The Gpx Family and Its Membersmentioning
confidence: 99%
“…GPx1 3p21.31 TFAP2C regulates GPx1 promoter through an AP-2 regulatory region [81] GPx1 polymorphism in modifying stress response [82] Decreased GPx1 expression [83] Loss of heterozygosity and allelic differences of GPx1 [88] Pro198Leu-associated decreased GPx1 activity with high breast cancer risk [89,92] The Leu198Leu genotype of GPx-1 [91] Regulate the sensitivity to doxorubicin [93] GPx2 14q23.3 Upregulated in breast cancer cells [19] Overexpression in rat breast cancer [98] Highly regulated by retinoic acid [94] GPx3 5q33.1 Downregulated in aggressive phenotype of breast cancer [103] An independent predictive marker for local recurrence of early-stage invasive cancer patients [104] GPx4 19p13.3 Downregulated in breast cancer cells [19] Predict poor prognosis of invasive ductal breast carcinoma [106] Impaired GPx4 expression in peripheral blood monocytes as a biomarker for increased breast cancer risk associated with an increased risk of breast cancer [91]. It is suggested that Leu carriers with the Pro198Leu GPx1 allele had a 1.9-fold increased risk of non-ductal breast cancer and a 2.6-fold increased risk of developing grade 3 ductal tumors [92].…”
Section: Gpxs Location Main Findings In Breast Cancers Referencesmentioning
confidence: 99%
“…Based on a transcriptomic and interactomic approach, a list of dysregulated selenoproteins was observed in two human HCC cell lines, HepG2 and Huh7, compared to normal human hepatocytes [18]. Moreover, we identified human miR-544a as able to modulate SELENOK expression in the two HepG2 and Huh7 cell lines [19], and also analyzed the selenoproteins' transcriptomes in MCF-7 and MDA-MB231 human breast cancer cell lines, compared to MCF10A normal epithelial breast cells [20]. Recently, we reported that elevated tumor tissue expression of the selenoprotein SEPHS2 in triple-negative breast cancer (TNBC) patients was correlated with the malignancy grade [21].…”
Section: Introductionmentioning
confidence: 99%